RANCANG BANGUN RUMAH PINTAR UNTUK PENGATURAN SISTEM PENERANGAN DAN JEMURAN OTOMATIS - Pratama, Mohamad Gatot; Rasmana, Susijanto Tri; Harianto, Harianto (Journal of Control and Network Systems (JCONES), 2017)
Along the changing times, the tech world has grown very quickly and rapidly. As a tool that works automatically at a factory or large corporations. Initially the only automation system is widely used in industry, but this time the automation system is also introduced in process automation in the home. Home automation system is also known as smart house or a smart home.In this final project created a system of home lighting design and the use of a clothesline automatically. At home lighting system will be used PIR sensor which serves to detect the presence of people and LDR sensors to turn on lights to capture the intensity of the light received. As for the drying system using rain sensors (Rain Sensor Arduino) which serves to detect rain and combined with LDR sensor to detect a lack of light or the weather is overcast. In this smart home design using microcontroller Arduino MEGA 2560 to configure each sensor is used. Testing smart house systems for automated lighting system and a clothesline, the results of testing for lighting outside the house, inside the house and found the clothesline in error by 16% and 84% of the system's success.Keyword : Smart Home, lighting system, clothesline automaticaly, Arduino MEGA 2560.